Anaplastic Transformation of Papillary Thyroid Cancer in the Retroperitoneum. (16th August 2015) - Solomon, James P.; Wen, Fang; Jih, Lily J.
Abstract : Anaplastic thyroid carcinoma is an aggressive variant of thyroid cancer that in most cases arises from anaplastic transformation of terminally differentiated thyroid carcinomas. This process usually occurs in the thyroid or cervical lymph nodes. Anaplastic transformation in distant metastatic sites is exceedingly rare, only previously documented in a few case reports. We report a rare case of anaplastic transformation of papillary thyroid carcinoma within a large retroperitoneal metastasis in a 64-year-old male 30 years after the initial diagnosis.